Papaya Jelly Candy Transforming Cancer Patients' Lives with Delicious Flavor and Extraordinary Benefits - Marlinda; Yona, Demandia; Zahirah, Naila; Larasati, Najwa Risha (Yayasan Rumah Ilmu Professor, 2025)
Cancer is a disease with profound physical, emotional, and economic impacts. One of the common challenges faced by cancer patients is malnutrition due to the side effects of treatments like chemotherapy and radiotherapy. Reduced appetite, nausea, and digestive issues often impede the recovery process. To address this, this study aims to develop papaya-based jelly candies that not only offer a delightful taste but also provide essential nutritional benefits for cancer patients. Papaya, rich in vitamin C, antioxidants, and the enzyme papain, plays a vital role in boosting the immune system and improving digestion. In this study, laboratory experiments were conducted to create a jelly candy formula using natural ingredients that are both easy to consume and beneficial for cancer patients. A sensory test with 50 participants revealed that papaya jelly candy was well-received in terms of taste, texture, aroma, and packaging. 80% of respondents reported an increase in appetite after consuming the candy, and 45% experienced a boost in energy and stamina. Furthermore, the papaya gummies demonstrated positive effects on digestion and immune function, which are critical benefits for cancer patients. This study highlights the potential of papaya jelly candy as a healthy, practical, and enjoyable nutritional supplement for cancer patients. Moving forward, the development of this product is expected to support nutritional therapy for cancer patients and open new avenues for innovation in functional food products made from natural ingredients